Appetite, the enteroendocrine system, gastrointestinal disease and obesity. Issue 1 (4th February 2021) - Crooks, Benjamin; Stamataki, Nikoleta S.; McLaughlin, John T.
Abstract : The enteroendocrine system is located in the gastrointestinal (GI) tract, and makes up the largest endocrine system in the human body. Despite that, its roles and functions remain incompletely understood. Gut regulatory peptides are the main products of enteroendocrine cells, and play an integral role in the digestion and absorption of nutrients through their effect on intestinal secretions and gut motility. Several peptides, such as cholecystokinin, polypeptide YY and glucagon-like peptide-1, have traditionally been reported to suppress appetite following food intake, so-called satiety hormones. In this review, we propose that, in the healthy individual, this system to regulate appetite does not play a dominant role in normal food intake regulation, and that there is insufficient evidence to wholly link postprandial endogenous gut peptides with appetite-related behaviours. Instead, or additionally, top-down, hedonic drive and neurocognitive factors may have more of an impact on food intake. In GI disease however, supraphysiological levels of these hormones may have more of an impact on appetite regulation as well as contributing to other unpleasant abdominal symptoms, potentially as part of an innate response to injury. Further work is required to better understand the mechanisms involved in appetite control and unlock the therapeutic potential offered by the enteroendocrine system in GI disease and obesity.